Periferia e arte: trajetórias de jovens artistas moradores do bairro do Jacintinho em Maceió/AL - Morais, Leila Samira Portela de (2017)
The dissertation aims to investigate what is the influence of art on the trajectories of young residents of the deep valleys located in a peripheral district of Maceió, Jacintinho. The neighborhood is marked by two major speeches, the media, portraying the district as violent and dangerous, and the speech of the residents, who claim the periphery as a place of art and culture. In this context, young people participate in a street theater group and try, through art, search for recognition and spaces of expression in an exclusive town like Maceio. Thus, the trajectories reveal what senses these young people attach to the place in which they live and how they construct a way to experience the youth. The neighborhood of Jacintinho stands out for its amount of artistic and cultural groups. Its streets and squares are constantly occupied by young people involved in various types of artistic and cultural manifestations. Those groups mobilized, through art, a series of speeches of identity and positive aspects of life on the periphery, in contrast to speeches often stigmatizing built outside these social spaces. Bourdieu is an importante author for us to understand these young people in their objective reality, because it is from their place of origin that they incorporate the world; that is, individuals internalize the objective world in accordance with the social position that they effectively occupy. However, the limits of this approach will be placed from the thought of Bernard Lahire, which offers a closer look at the plurality of socializing experiences that the same actor is submitted along his trajectory.